The Mormon Battalion: U.S. Army of the West, 1846-1848 - Ricketts, Norma Baldwin, author; Utah State University Press, publisher (Colorado State University. Libraries, 1996)
Few events in the history of the American Far West from 1846 to 1849 did not involve the Mormon Battalion. The Battalion participated in the United States conquest of California and in the discovery of gold, opened four major wagon trails, and carried the news of gold east to an eager American public. Yet, the battalion is little known beyond Mormon history. This first complete history of the wide-ranging army unit restores it to its central place in Western history, and provides descendants a complete roster of the Battalion's members.
Foreword / David L. Bigler -- 1. The Enlistment -- 2. Fort Leavenworth: Knapsacks and Muskets -- 3. Santa Fe: Colonel Cooke Assumes Command -- 4. Pima and Maricopa Indian Villages -- 5. San Diego: Company B Makes Friends -- 6. Los Angeles: Building Fort Moore -- 7. General Kearny's Escort to Fort Leavenworth -- 8. After Discharge -- 9. Monterey, San Francisco, and the Brooklyn -- 10. Sutter's Workmen -- 11. Journey's End -- 12. Detached Service -- 13. Mormon Volunteers -- App. A. Analysis of Movement within Mormon Battalion -- App. B. Alphabetical Reconstructed Roster -- App. C. Men Who Reached California -- App. D. Hancock-Los Angeles Company -- App. E. Hancock-Sierra Company -- App. F. Sutter's Workmen -- App. G. Purchase of Sutter's Russian Cannon -- App. H. Military Documents -- App. I. Music and Poetry.
Keywords: Mexican War, 1846-1848 -- Campaigns -- Southwest, New; Mexican War, 1846-1848 -- Campaigns -- California; Mexican War, 1846-1848 -- Regimental histories; Mexican War, 1846-1848 -- Participation, Mormon; Mormons -- Southwest, New -- History; Southwest, New -- History, Military; California -- History, Military; United States. Army. Mormon Battalion -- History; United States. Army. Mormon Battalion -- Registers